Erosão hídrica de Latossolo Vermelho muito argiloso relevo ondulado em área de pós-plantio de eucalipto no Vale do Rio Doce, região Centro Leste do Estado de Minas Gerais - De Figueiredo Brito, Liziane [UNESP]; Silva, Marx Leandro Naves; Curi, Nilton; Leite, Fernando Palha; Ferreira, Mozart Martins; Pires, Lislane Souza (My University, 2005)
The erosion caused by running water constitutes important cause of environmental degradation and productivity reduction, which justifies its evaluation in areas of eucalypt commercial plantations, mainly in ondulated slope conditions. The present study was intended to evaluate the influence of different management systems, in an undulated eucalypt pos-planting area, upon soil and water losses by erosion. The experiment was installed in a very clayey Red Latosol (Oxisol) under three eucalypt management systems (downhill planting with burning of crop residues - EDq; downhill planting with maintenance of crop residues on soil surface - ED; level planting with maintenance of crop residues on soil surface - EN), native forest (FN), bare soil (SD), and native pasture (PN). The soil and water losses evaluations were performed in standard plots installed in the field. All eucalypt systems presented very low values of soil losses in relation to the established tolerance limit, indicating the adequacy of these management systems concerning water erosion. The sustainability of these environments regarding erosion is indicated by the fact that soil losses in eucalipt were very close to those observed in native forest (reference).
Water erosion of very clayey Red Latosol (Oxisol) in an undulated area of eucalypt post-planting at Rio Doce Valley, Center East region of Minas Gerais State, Brazil
Keywords: Eucalypt; Management; Oxisol; Water erosion; Soil losses; Crops; Degradation; Forestry; Plants (botany); Soil mechanics; Water resources; Erosion; Farm Crops; Plants; Soil Mechanics; Water Resources